Wisdom in Controversy: Paradox and the Paradoxical in Sayings of Abū Yazīd al-Bisṭāmī (d. 234/848 or 261/875) - Keeler, Annabel (Journal of Sufi studies, 2018)
Sufi authors, such as Abū Naṣr al-Sarrāj (d. 378/998) and Ruzbihan Baqlī (d. 606/1209), were concerned to explain the shaṭḥiyyāt, often translated as "ecstatic utterances", of earlier mystics and defend them against the condemnation they received from those who had neither the experience nor the purview to understand them. Among the shaṭḥiyyāt explained by these two authors are a number of the most infamous utterances of Abū Yazīd al-Bisṭāmī. Yet the controversial speech of Abū Yazīd (or Bāyazīd) appears not to have been limited to that which he uttered in a state of ecstasy, nor were those who objected to such speech solely the scholars of outward knowledge, as is commonly held. Drawing on the corpus of sayings attributed to Bāyazīd and anecdotes about him as recorded in some of the earliest available sources, this essay will look more closely at reports of his engagement with his contemporaries and reasons why he may have been at odds with certain groups in the community. It will consider the significance some of his most controversial and paradoxical sayings, as well as the contradictory nature of some of his own statements about himself, bombastic and apparently boastful on the one hand, and extremely self-critical on the other. Lastly it will consider the shatḥ (plural shaṭaḥāt or shaṭḥiyyāt), its definition by Sufis and the aptness of its translation by French scholars, starting with Henri Corbin, as "paradoxe".